ADEQUAR O CURRÍCULO ESCOLAR PARA ALUNOS COM NECESSIDADES ESPECÍFICAS DE APRENDIZAGEM: POR QUE E COMO FAZER - Lúcia Moreira Gomes, Maria (LINKSCIENCEPLACE, 2026)
The laws which relate to education and citizenship as a whole can anticipate education for all. In Brazil, this statement is restricted to the role and the few institutions with repo education and teacher training. In this work are made some reflections about the education of people with disabilities, whose theme, already so exploited, does not exhaust its theories and actions, in view of the new approaches and the insertion of new studies, as the neuroscience, and also the new technologies that in have greatly contributed to that successive changes occur, as must be the dynamic process of education. The adaptation or curricular adequacy has focus in this work by understanding that it is an integral part of a process of an education that welcomes.